PERAN KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI DINAS PERHUBUNGAN KABUPATEN SITUBONDO - Amalia, Rizky Nur; Pramitasari, Riska Ayu; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The Situbondo Regency Government includes the Transportation Agency as one of its departments. At the beginning of its operation, the Transportation Department was mainly responsible for controlling land traffic, regulating parking facilities, and protecting district mobilization operations. For the Dinas Perhubungan of Situbondo Regency to maximize its employees, everyone involved must understand role responsibilities, reporting relationships, organizational structure, and standard operating procedures. This is stated in the related Situbondo Regency Regent Decree (PERBUP) Number 24 of 2022. This study aimed to analyze and examine the role of leadership, motivation, and work discipline on employee performance through job satisfaction as an intervening variable at the Situbondo Regency Transportation Officeâ€. This research is quantitative. The population used in this study was 51 employees. The sampling technique used was saturated sampling. This studyâ€™s data analysis and hypothesis testing used the Structural Equation Method - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that leadership has a significant positive effect on job satisfaction, work motivation has a significant positive effect on job satisfaction, work discipline has a significant positive effect on job satisfaction, leadership has a negative but insignificant effect on performance, work motivation has a positive but insignificant effect on performance, work discipline has a negative but insignificant effect on performance, job satisfaction has a significant positive effect on performance. The results of the indirect effect hypothesis test show that the Leadership variable on performance through job satisfaction has a significant positive effect, motivation on performance through job satisfaction has a significant positive effect, and work discipline on performance through job satisfaction has a significant positive effect.